2006
DOI: 10.1128/aac.00198-06
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Invasive Streptococcus pneumoniae Isolates in Portugal over an 11-Year Period

Abstract: Streptococcus pneumoniae is an important pathogen responsible for serious invasive diseases, including meningitis and septicemia. The spread of multidrug-resistant (MDR) pneumococci has become a worldwide problem, making treatment more difficult (18). Indeed, in addition to resistance to penicillin, resistance to other antibiotics, including erythromycin, tetracycline, and chloramphenicol, has emerged and is spreading (10).Since 1989, the National Institute of Health Dr. Ricardo Jorge reference laboratory has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
3
11
0
4
Order By: Relevance
“…The highest antimicrobial nonsusceptibility prevalences were seen among pneumococci isolated from children less than 15 years old, particularly those less than 2 years of age. This may be explained by the high consumption of antimicrobials among young children, compared to other age groups (4), and is in accordance with studies from other countries (18,21).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The highest antimicrobial nonsusceptibility prevalences were seen among pneumococci isolated from children less than 15 years old, particularly those less than 2 years of age. This may be explained by the high consumption of antimicrobials among young children, compared to other age groups (4), and is in accordance with studies from other countries (18,21).…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, reduced ceftriaxone susceptibility (the meningitis breakpoint) was detected in 3 to 4% of the isolates, which warrants careful continuous surveillance in the future. In countries with high PEN R prevalence, such as Taiwan, the United States, and Spain, 6 to 9% of the pneumococci are nonsusceptible to ceftriaxone (9,33,58), while in countries with low PEN R prevalences, such as Italy, Hungary, and Portugal, the respective proportion is below 1% (18,27,39). However, comparing the studies is sometimes difficult because of differences in the representativeness of the isolates and the breakpoints used.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The frequency of multidrug resistance in this study is much higher than those reported previously among large numbers of systematically collected invasive pneumococcal isolates from South Africa up to 1998 (16,22,33) but lower than levels observed in an international multicenter survey using both limited invasive and respiratory isolates from South Africa in 2004 (14). The significant increase in multidrug resistance observed over the 6-year period of our study is consistent with trends reported in other prevaccine era studies (10,22,55), suggesting that the problem of MDR IPD is worsening.…”
Section: Discussionsupporting
confidence: 74%
“…La prevalencia mundial de resistencia en S. pneumoniae a las fluoroquinolonas es inferior al 2% (3,5,6,(30)(31)(32)(33)(34). Sin embargo, algunos estudios reportan mayores prevalencias, como el realizado en Canadá que informó un incremento en la resistencia a ciprofloxacino de más del 1% en 1997 a 4,2% en el 2005 y a levofloxacina de 0,2 a 1,1% en el mismo periodo (23).…”
Section: Discussionunclassified